Binary Typing of Staphylococcus aureus Strains through Reversed Hybridization Using Digoxigenin-Universal Linkage System-Labeled Bacterial Genomic DNA - van Leeuwen, Willem (American Society for Microbiology, 2001)
A novel binary typing (BT) procedure, based on reversed hybridization of digoxigenin-universal linkage system-labeled bacterial DNA to strip-immobilized probes, is presented. Chromogenic detection of hybrids was performed. Staphylococcus aureus isolates (n = 20) were analyzed to establish the feasibility of BT. A technically simple and fast procedure has been developed for application in routine microbiology laboratories.